2020
DOI: 10.1155/2020/2381462
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Modified Duhuo Jisheng Decoction in the Treatment of Lumbar Disc Herniation: A Systematic Review and Meta‐Analysis

Abstract: Objective. Lumbar disc herniation (LDH) is based on the degenerative changes of the intervertebral disc. Many drugs are used to treat and prevent LDH, including Western medicine and Chinese medicine. Duhuo Jisheng Decoction (DHJSD) is one of the most classic Chinese medicine prescriptions. The purpose of our meta-analysis is to evaluate the efficacy and safety of modified DHJSD in the treatment of LDH. Methods. We searched multiple databases includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…The combination of these herbs can eliminate pathogenic factors and play the role of removing rheumatism, relieving arthralgia, tonifying the liver and kidneys and supplementing qi and blood. At present, DHJSD is broadly employed in the clinical treatment of lumbar disk herniation because of its anti-inflammatory and analgesic effects [25,26]. A meta-analysis showed that modified DHJSD had a more favorable effect on the treatment of lumbar disk herniation than Western medicine, and there were no obvious adverse events [25].…”
Section: Introductionmentioning
confidence: 99%
“…The combination of these herbs can eliminate pathogenic factors and play the role of removing rheumatism, relieving arthralgia, tonifying the liver and kidneys and supplementing qi and blood. At present, DHJSD is broadly employed in the clinical treatment of lumbar disk herniation because of its anti-inflammatory and analgesic effects [25,26]. A meta-analysis showed that modified DHJSD had a more favorable effect on the treatment of lumbar disk herniation than Western medicine, and there were no obvious adverse events [25].…”
Section: Introductionmentioning
confidence: 99%
“…DHJSD is a TCM recorded in Bei Ji Qian Jin Yao Fang of the Tang Dynasty for the treatment of “Bi Zheng,” usually consisting of the following 15 herbs, including Du Huo ( Radix Angelicae Pubescentis ), Sang Ji Sheng ( Herba Taxilli ), Qin Jiao ( Radix Gentianae Macrophyllae ), Fang Feng ( Radix Saposhnikoviae ), Xi Xin ( Herba Asari ), Fu Ling ( Poria Cocos ), Chuan Xiong ( Rhizoma Chuanxiong ), Bai Shao ( Radix Paeoniae Alba ), Du Zhong ( Cortex Eucommiae Ulmoidis ), Ren Shen ( Panax Ginseng ), Gan Cao ( Radix Glycyrrhizae ), Dang Gui ( Radix Angelicae Sinensis ), Niu Xi ( Radix Achyranthis Bidentatae ), Shu Di Huang ( Radix Rehmanniae Preparata ), and Rou Gui ( Cortex Cinnamomi ) [ 10 ]. Among them, Du Huo has the good effects of relieving the pain of “Bi Zheng,” dispelling cold and dehumidification, nourishing blood and Qi; Xi Xin, Fang Feng, and Qin Jiao dispel rheumatism, relax tendons and muscles, and benefit joints; Sang Ji Sheng, Du Zhong, Rou Gui, and Niu Xi nourish liver and kidney and strengthen bones and muscles; Dang Gui, Bai Shao, Shu Di Huang, and Chuan Xiong promote blood circulation; Ren Shen, Gan Cao, and Fu Ling strengthen spleen and supplement Qi [ 11 ]. The combination of the above herbs forms DHJSD, the classic bone injury prescription in TCM, it has the effect of nourishing the liver and kidney, benefiting Qi and blood, and stopping the pain of “Bi Zheng”, which obviously improves the microcirculation of the body [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…And the cause of osteoporosis is the deficiency of Qi and blood in the liver and kidney and the loss of nutrition in the tendons and bones, so the treatment should be to nourish the liver and kidney and strengthen the tendons and bones as the primary treatment [ 14 ]. Therefore, DHJSD has been widely used in China to treat rheumatoid arthritis, intervertebral disc disease, knee osteoarthritis, and osteoporosis, especially postmenopausal osteoporosis [ 2 , 11 , 14 17 ]. However, due to the ingredients contained, the mechanism of action of TCM is often elusive.…”
Section: Introductionmentioning
confidence: 99%
“…The characteristics of IVDD are complex, with pathological changes in NP and inner ring, forming cracks radiating from the central area of the intervertebral disc to the periphery (Fraser et al, 1993). The clinical symptoms of IVDD are mainly based on the degenerative changes of the intervertebral disc, leading to long-term lumbago and leg pain, neurological deficits, and loss of labor ability, which seriously affect the life quality of patients (Xiong et al, 2020). Caused by accumulation of injury on the basis of degenerative diseases, IVDD will further repeatedly attack the degeneration of the intervertebral disc.…”
Section: Introductionmentioning
confidence: 99%